Critiquing complexity and contradiction in Architecture - Jonathan Ochshorn (Agathón)
This paper challenges the idea that complex building geometries reflect the complexity of contemporary life; it does so by examining Complexity and Contradiction in Architecture, Robert Venturi’s seminal work from 1966, as well as later writings by advocates of a computationally-driven complexity. The essay shows that: a) complexity, rather than being defined absolutely, is relative in everyday speech; b) complexity, as defined in natural systems, cannot be extrapolated to human behavior; c) modern life is becoming simpler, rather than more complex; d) complexity is typically embedded within products and systems and, as such, inaccessible to ordinary consciousness; e) architectural complexity reflects a competitive drive for notoriety associated with avant-garde production, and leads to energy-inefficient buildings with an increased risk of control layer failure.